Karren above Custonaci (Sicily, Italy) - Knez, Martin; Ruggieri, Rosario; Slabe, Tadej (Acta Carsologica, 2019)
The extremely interesting karst of the Capo San Vito area in western Sicily displays the majority of the distinct characteristics of the three-dimensional landscape: karst surfaces, caves, unique water trickling systems, and maritime development (Ruggieri, 2009, 2015). By the sea as well as higher in the hinterland, the surface is mostly karren-like. This part of the planned study of the formation of the entire rock surface of this karst presents the results of studying the slope karren above Custonaci. They reveal the development of karren from subsoil karren and the characteristic formation of the karst surface in this area and on this rock. Keywords: karren, lithology, rock relief, Sicily, Italy Škraplje nad Custonacijem (Sicilija, Italija) Nadvse zanimiv kras področja Capo San Vito na zahodu Sicilije ponuja večino izrazitih značilnosti trirazsežne pokrajine, kraško površje, jame in svojevrstno pretakanje vode ter obmorski razvoj (Ruggieri 2009, 2015). Površje je večinoma škrapljasto, tako ob morju kot v višjem zaledju. Tokrat so pri načrtovani proučitvi oblikovanja celotnega skalnega površja tega krasa predstavljeni izsledki proučevanja pobočnih škrapelj nad Custonacijem. Razkrivajo razvoj škrapelj iz podtalnih škrapelj in značilno oblikovanje kraškega površja v tem okolju in kamnini. Ključne besede: škraplje, litologija, skalni relief, Sicilija, Italija.